Ответ:a=5Pi/6+Pi*n
а=-Pi/6+Pi*n
Объяснение:
3) tg(Pi/2-a)=-корень из 3
-tg(a-Pi/2)=-корень из 3/*-1
tg(a-Pi/2)=корень из 3
а-Pi/2=Pi/3+Pi*n
a=Pi/2+Pi/3+Pi*n
a=3Pi/6+2Pi/6+Pi*n
a=5Pi/6+Pi*n
4) tga=-корень из 3/3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:a=5Pi/6+Pi*n
а=-Pi/6+Pi*n
Объяснение:
3) tg(Pi/2-a)=-корень из 3
-tg(a-Pi/2)=-корень из 3/*-1
tg(a-Pi/2)=корень из 3
а-Pi/2=Pi/3+Pi*n
a=Pi/2+Pi/3+Pi*n
a=3Pi/6+2Pi/6+Pi*n
a=5Pi/6+Pi*n
4) tga=-корень из 3/3
а=-Pi/6+Pi*n